Application of planar laser-induced fluorescence for the investigation of interfacial waves and rivulet structures in liquid films flowing down inverted substrates - Markides,C; Charogiannis,A (Interfacial phenomena and heat transfer, 2017)
We investigate the interfacial topology of liquid-film flows falling under an inverted planarsubstrate by conducting space- and time-resolved film-height measurements. A planarlaser-induced fluorescence (PLIF) technique is employed for this purpose, with a twocameraarrangement that allows us to image a region of the flow extending ≈ 40 mm oneither side of the centre of the film span, at a distance 330 mm downstream of the flowinlet. The substrate inclination angle is set to β = −30 °, the working fluid comprises 82%glycerol and 18% water (by weight), and the flow Reynolds number, Re, is varied in therange Re = 0.6 − 8.2. The uncertainty associated with the instantaneous film-height measurementis estimated at less than 3%. Depending on the flow Re, we observe a range ofinteresting flow regimes typically characterised by pronounced rivulet formation and spatiotemporalcoherence, which deviate from expectations of liquid-films flows falling overplanar substrates. Over the range Re = 0.6 − 3.5, a series of regime transitions take place,followed by the generation of regular, in both space and time, 3-D solitary pulses ‘riding’over rivulet flow structures. These waves grow with increasing flow Re, as more liquidis drawn away from the rivulet troughs due to gravity. Finally, the wave frequencies andrivulet wavelengths are investigated by employment of power spectral density (PSD) andwavelet analyses. The application of PSD analysis offers superior resolution in the frequencydomain when performed on temporally varying film-height data, whereas waveletanalysis is preferred when considering the spatially varying film-height data due to thelimited spatial extent and low number of captured rivulets in the imaged region.